Selection and Verification of Kenaf Fibres as an Alternative Friction Material Using Weighted Decision Matrix Method - Mustafa, Ashafi'e; Abdollah, Mohd Fadzli bin; Shuhimi, Fairuz Fazillah; Ismail, N.; Amiruddin, Hilmi; Umehara, Noritsugu (Elsevier, 2014)
Nowadays, natural fibres composites are widely investigated and acknowledged as materials which minimise carbon dioxide produced in all phases of their interaction with environment compared to glass fibres composites. However, the fibres selection is still based on economic factors and local availability rather than dependency on a systematic approach. Therefore, this paper suggests a study on how kenaf fibres is verified compared to other natural fibres that could potentially be used as an alternative source of friction material (FMs) using the Weighted Decision Matrix (WDM) approach. The method of selection is to consider the impact on the environment and human health. An exhaustive review of potential natural fibres and friction materials is presented and suggested for future development direction. The result shows that WDM method verifies the suggested suitability of kenaf fibres.